2006
DOI: 10.2353/ajpath.2006.051365
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heme Oxygenase-1 in Murine Melanoma

Abstract: Heme oxygenases (HOs) catalyze the oxidation of heme to the biologically active products carbon monoxide (CO), biliverdin, and ferrous iron. Two distinct variants of HOs have been described in humans and rodents, each encoded by a different gene: HO-2, which is constitutively expressed, and HO-1, which is potently induced in many cell types by heme, inflammatory cytokines, and oxidative stress-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 81 publications
6
93
1
Order By: Relevance
“…Targeted inhibition of HO by polyethylene glycol-linked ZnPP showed growth inhibitory activity against solid Sarcoma-180 tumours in mice (Fang et al 2003). Precise mechanisms as to how the HO/CO system promotes tumour growth are not fully understood, but widespread processes including the induction of resistance to stress and apoptosis (Doi et al 1999;Liu et al 2004;Was et al 2006), the altered expression of cell cycle and differentiation genes Koiso et al 2000;Chauveau et al 2005;Zwerina et al 2005), and the promotion of angiogenesis (Cherrington et al 2000;Dulak et al 2002;Sunamura et al 2003;Cisowski et al 2005;Hirai et al 2007;Deshane et al 2007) have been suggested (Fig. 3).…”
Section: Ho Activation In Cancerous Conditionsmentioning
confidence: 98%
“…Targeted inhibition of HO by polyethylene glycol-linked ZnPP showed growth inhibitory activity against solid Sarcoma-180 tumours in mice (Fang et al 2003). Precise mechanisms as to how the HO/CO system promotes tumour growth are not fully understood, but widespread processes including the induction of resistance to stress and apoptosis (Doi et al 1999;Liu et al 2004;Was et al 2006), the altered expression of cell cycle and differentiation genes Koiso et al 2000;Chauveau et al 2005;Zwerina et al 2005), and the promotion of angiogenesis (Cherrington et al 2000;Dulak et al 2002;Sunamura et al 2003;Cisowski et al 2005;Hirai et al 2007;Deshane et al 2007) have been suggested (Fig. 3).…”
Section: Ho Activation In Cancerous Conditionsmentioning
confidence: 98%
“…However, the abnormally elevated expression and activity of this enzyme have been often reported in several tumor tissues, which may influence cancer cell proliferation, invasion and metastasis. In line with this notion, the overexpression of HO-1 enhanced viability, proliferation, and metastatic potential of melanoma cells [13]. HO-1 also stimulates angiogenesis through upregulation of vascular endothelial growth factor and overproduction of pro-angiogenic carbon monoxide [14].…”
Section: Introductionmentioning
confidence: 99%
“…Completed physician-initiated studies with inhaled CO in human volunteers were performed in acute lung inflammation and COPD where anti-inflammatory effects were observed [7981], but these studies did not evaluate careful dose ranging. Clearly, there is a great deal of work yet to be done to understand the therapeutic potential of HO-1 and CO in a clinically useful modality, particularly because there are a handful of reports arguing that increased inhibition of HO-1 can also be beneficial in certain cancers [8284]. …”
Section: Discussionmentioning
confidence: 99%